Fasting Upregulates npy, agrp, and ghsr Without Increasing Ghrelin Levels in Zebrafish (Danio rerio) Larvae - Opazo, Rafael; Plaza-Parrochia, Francisca; Cardoso dos Santos, Gustavo R.; Carneiro, Gabriel R. A.; Sardela, Vinicius F.; Romero, Jaime; Valladares, Luis (Frontiers in Physiology, 2019)
Food intake in fish and mammals is orchestrated by hypothalamic crosstalk between orexigenic (food intake stimulation) and anorexigenic (food intake inhibition) signals. Some of these signals are released by peripheral tissues that are associated with energy homeostasis or nutrient availability. During the fish larva stage, orexigenic stimulation plays a critical role in individual viability. The goal of this study was to assess the mRNA levels of the main neuropeptides involved in food intake regulation (npy, agrp, carppt, and pomc), in concert with the mRNA levels and peptide levels of ghrelin, under a fasting intervention at the larval stage in zebrafish (Danio rerio). Prior to the fasting intervention, the zebrafish larva cohort was reared for 20 days post fertilization (dpf) and then randomly divided into two groups of 20 individuals. One group was subjected to a fasting intervention for 5 days (fasted group), and the other group was fed normally (fed group); this experimental protocol was performed twice independently. At the end of the fasting period, individuals from each experimental group were divided into different analysis groups, for evaluations such as relative gene expression, immunohistochemistry, and liquid chromatography coupled to nano high-resolution mass spectrometry (nLC-HRMS) analyses. The relative expression levels of the following genes were assessed: neuropeptide Y (npy), agouti-related peptide (agrp), proopiomelanocortin (pomc), cocaine and amphetamine-regulated transcript (cartpt), ghrelin (ghrl), ghrelin O-acyltransferase (mboat4), growth hormone secretagogue receptor (ghsr), and glucokinase (gck). In the fasted group, significant upregulation of orexigenic peptides (npy – agrp) and ghsr was observed, which was associated with significant downregulation of gck. The anorexigenic peptides (pomc and cartpt) did not show any significant modulation between the groups, similar to mboat4. Contrary to what was expected, the relative mRNA upregulation of the orexigenic peptides observed in the fasted experimental group could not be associated with significant ghrelin modulation as assessed by three different approaches: qPCR (relative gene expression of ghrelin), nLC-HRMS (des-acyl-ghrelin levels), and immunohistochemistry (integrated optical density of prepropeptides in intestinal and hepatopancreas tissues). Our results demonstrate that zebrafish larvae at 25 dpf exhibit suitable modulation of the relative mRNA levels of orexigenic peptides (npy and agrp) in response to fasting intervention; nevertheless, ghrelin was not coregulated by fasting. Therefore, it can be suggested that ghrelin is not an essential peptide for an increase in appetite in the zebrafish larva stage. These results give rise to new questions about food intake regulation factors in the early stages of fish.